Loans Disbursement and the Underlying Challenges Among Women’s Village Community Banks (VICOBA) in Meru District of Arusha-Tanzania - Luvinga, Kepha Charles (Advances in Social Sciences Research Journal, 2025)
This study investigates the Loans disbursement and the underlying challenges among Women’s Village Community Banks (VICOBA) in Arumeru district of Arusha- Tanzania. A cross-sectional study design was employed, with data collected at a single point during the research period. Simple random sampling was utilized to select 90 members within Women VICOBA groups. The sample was obtained from Kingosina, Kilindi, Filadefia, Tuombe, Ukarimu, and Uzima VICOBA groups.Data were gathered through questionnaires analyzed descriptively using SPSS V. 21 software. The findings of this study highlight the significant role that VICOBA plays in enhancing financial inclusion and economic empowerment among women in Meru district. Women are primarily motivated to join VICOBA due to its accessibility, affordability, and flexibility in loan repayment, allowing them to save, access credit, and invest in income-generating activities. However, challenges such as loan repayment difficulties, delayed payments, financial mismanagement, and inequality in loan distribution hinder the effectiveness and sustainability of these groups. With this findings, the study recommends strengthening VICOBA by ensuring that the key stakeholders including the government and its regulatory institutions provides clear frameworks which will facilitate the institutional efficiency among all VICOBA groups without affecting their flexibilities in providing financial services to their members.